(untitled) (Journal of Business Management and Accounting, 2015)
In view of the present rapid changing of technology and economic landscapes, the Research and Development (R&D) field has garnered more attention than before throughout the world. Industrial innovation in this knowledge-driven era demands R&D as the undisputable key for improvement and to maintain competitiveness. Parallel to the industrial and economic growths, more and more researchers and skilled workers are required to fill in the specific fields all over the globe. The growing numbers of R&D facilitiesand personnel, however, is unable to provide assurance that improvement would take place after a particular research result is implemented. R&D laboratories themselves are systems that process inputs and generate outputs, where in the process, inevitable challenges are encountered to ensure that the task is not only capable of solving particular problems, but also to ensure positive and innovative outcomes. R&D is also subject to performance analysis to measure the effectiveness, accomplishments, and productivity amongst others, because performance is an importance element in grant disbursement. In doing so, R&D evaluation is an important aspect and practised in most parts of the world with different methods and strategies. This paper reports an R&D overview and explores the need of the global community for post decision evaluation to ensure that the decision is sustainable in the long run.